A Corpus-Based Comparative Study of Arabic and English Prepositions among Arabic-Speaking EFL Learners in the Saudi Context - Alhothaly, Marzoog (International Journal of Linguistics, Literature and Translation, 2026)
Prepositions play a crucial role in English for expressing relationships of time, place, manner, and possession; however, they can be challenging for Arabic-speaking learners due to the syntactic and semantic differences in structure. This study scrutinises how Saudi EFL learners use English prepositions and compares their usage with that of native English writers. Corpus-based approaches (CBAs) have been utilised for identifying the cooccurrence of prepositions in learner text. The study compiled 500 written texts (150,000 words) in the Arabic Learner Corpus (ALC) and 2,761 texts (6.9 million words) in the British Academic Written English (BAWE). The study’s key findings reveal that in the writings of English learners whose first language is Arabic, the preposition لـ / li (“for, to”) appears 2614.08 times, بـ / bi (“with, by, in”) appears 285.25 times, and كَ / ka (“like, as”) occurs 187.14 times. In contrast, the prepositions فوق / fawq (“above, over”) appear only 0.66 times, تحت / taḥta (“under, beneath”) 0.87 times, and أثناء / athnā’ (“during”) 0.87 times in learner writing. On the other hand, the most frequently occurring English prepositions are to (67.23), of (39.26), for (31.71), as (24.06), by (23.79), with (21.85), and in (22.21). The least commonly used prepositions include beneath (0.01), beyond (0.13), and concerning (0.13), along with other low-frequency items such as upon (0.37) in BAWE. The findings demonstrate that first language influence and limited exposure to abstract prepositions contribute to these patterns. This study fills a research gap and provides the empirical evidence to guide pedagogical strategies that target underused prepositions in Saudi EFL contexts.